Circular dichroism of some high-symmetry chiral molecules: B3LYP and SAOP calculations - ALTUN, ZİKRİ (SPRINGER, 2009)
Computational modeling of optical activity, circular dichroism (CD) and optical rotatory dispersion, is rapidly becoming a useful supplement to experimental studies of absolute configuration. Here, we investigate the predictions of two alternative formulations of the rotational strength based on time-dependent density functional theory (TD-DFT), for a series of high symmetry chiral systems. We employ the TD-DFT method as realized in Gaussian 03 suite with the hybrid functional B3LYP and as incorporated in the Amsterdam density functional (ADF) suite with PBE and SAOP functionals. The high-symmetry systems described here are somewhat larger than those used to evaluate the influence of basis sets and density functional choice, and for such large systems the very extensive basis sets recommended by most investigators may not be suitable for routine use. We observe that useful results for these systems can be obtained in modest bases, and in particular that diffuse functions may not be required for informative use of the ADF implementation. The statistical average of orbital potentials (SAOP) model developed by Baerends is essential to the success of the ADF implementation. In some cases chirality is defined by features of the molecular structure remote from the chromophore. This is a severe test of the TD-DFT theory, since high-lying excitations define the most prominent features of the CD spectra, and complicates the use of computations to guide the assignment of absolute configuration. Experimental investigation of the high symmetry systems described here is desirable.
Keywords: DENSITY-FUNCTIONAL THEORY; AB-INITIO CALCULATION; OPTICAL-ROTATION; ELECTRONIC-ABSORPTION; THEORETICAL ASPECTS; SPECTRA; 9,9-SPIROBIFLUORENE; STEREOCHEMISTRY; CONFIGURATION